Magnetic susceptibility variations of the Ediacaran cap carbonates in the Yangtze platform and their implications for paleoclimate - 吴怀春 张世红 蒋干清 李海燕 (Chinese journal of oceanology and limnology, 2005)
Magnetic susceptibility (MS) data were obtained from 11 sections of the Doushantuo (Ediacaran) cap carbonate that directly overlies the Nantuo glacial diamictite in the southeastern margin of the Yangtze platform. The MS data revealed two regionally correlatable peaks at the bottom and top of the cap carbonate, separated by an interval of low values. The lower MS peak coincides with high percentage of insoluble siliciclastic residues that are compositionally identical to the matrix of the underlying diamictite, suggesting its origin controlled mainly by detrital components during the first phase of cap carbonate deposition at the end of the glaciation. The upper MS peak is associated with high clay content and iron sulfides, and can be interpreted as either derived from enhanced greenhouse weathering that could have brought more terrigenous components into the ocean, or the result of ocean anoxia at the late stage of cap carbonate deposition that could led to formation of abundant iron sulfides. The regionally consistent MS curves from the cap carbonates provided the first geophysical record for the rapid climate change from icehouse to greenhouse conditions in the aftermath of the Neoproterozoic “snowball Earth” event.